PSYCHOLOGICAL CAPITAL MEDIATION AND PEER SUPPORT MODERATION IN ENTREPRENEURIAL INTENTION - Yusmedi Nurfaizal; Mugiarti Mugiarti (Jurnal Manajemen dan Kewirausahaan, 2026)
Entrepreneurial intention research remains fragmented, often emphasizing isolated personal traits while overlooking the psychological and social mechanisms that translate capabilities into sustained entrepreneurial drive. This study addresses that limitation by examining how creativity, risk taking propensity, and digital literacy influence entrepreneurial intention through psychological capital, with peer support acting as a contextual amplifier. Using survey data from 250 undergraduate students and analyzed via PLS-SEM, the findings demonstrate that psychological capital serves as a pivotal resource mechanism converting individual competencies into entrepreneurial motivation. Moreover, peer support strengthens the capacity of psychological capital to shape intention, highlighting the interactive role of internal and external resources. The study advances the literature by repositioning psychological capital from a mere predictor to a mediating engine that channels capabilities into intention, while conceptualizing peer support as a boundary condition that enhances resource deployment. Theoretically, this refines resource based and social capital perspectives by integrating personal competencies, psychological assets, and social context into a unified explanatory model. Practically, it suggests that entrepreneurship education must simultaneously cultivate digital competence, psychological capital, and structured peer ecosystems to effectively stimulate entrepreneurial readiness.